Analisis Peningkatan Hasil Belajar Gerak Lurus Melalui Penerapan Simulasi Ophysics Dalam Model Problem Based Learning - Vira, Patrisia; Angraeni, Lia; Nurussaniah, Nurussaniah (Jurnal Inovasi Pendidikan dan Pengajaran (JIPP), 2025)
Physics learning, particularly on the topic of linear motion, often encounters challenges related to students’ low conceptual understanding due to limited laboratory facilities and insufficient use of interactive learning media. Digital simulations such as oPhysics offer a promising alternative to virtual laboratories by providing concrete visualizations of kinematic phenomena. This study aims to analyze the improvement of students’ learning outcomes on linear motion through the implementation of the oPhysics simulation integrated into a Problem Based Learning (PBL) model. The research employed a pre-experimental method with a One-Group Pretest–Posttest design involving 30 eleventh-grade students. The instrument consisted of seven validated multiple-choice items measuring cognitive abilities at levels C1–C4. Data were analyzed using the Wilcoxon Signed Rank Test after normality tests indicated non-normal distribution. The results show a significant improvement in students’ learning outcomes, with the average score increasing from 34.20 to 74.58 and a significance value of p = 0.000 (p < 0.05). The integration of oPhysics within PBL allows students to manipulate motion variables and observe the effects directly, supporting deeper conceptual understanding and more effective problem-solving activities. These findings highlight that combining digital simulations with problem-based instructional approaches can enhance the quality of physics learning, particularly in understanding linear motion concepts.